2020
DOI: 10.3390/insects11110748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lethal Bronzing Disease, Palm Height, and Temperature on Abundance and Monitoring of Haplaxius crudus

Abstract: Insect vector feeding preference and behavior play important roles in pathogen transmission, especially for pathogens that solely rely on insect vector transmission. This study aims to examine the effects of the 16SrIV-D phytoplasma, the causal agent of lethal bronzing (LB) disease of palms, on associated auchenorrhynchan insects. The numbers of auchenorrhynchans collected during weekly surveys during a yearlong study using yellow sticky traps were analyzed. The cumulative number of H. crudus was 4.5 times gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…P. aculeata’ ( Howard et al 1983 ). Unlike other insects, H. crudus appears to display a preference for phytoplasma-infected palms compared to healthy palms in field settings ( Mou et al 2020b ). Haplaxius crudus collected from population surveys in Mexico and Florida tested positive for ‘ Ca.…”
Section: Introductionmentioning
confidence: 99%
“…P. aculeata’ ( Howard et al 1983 ). Unlike other insects, H. crudus appears to display a preference for phytoplasma-infected palms compared to healthy palms in field settings ( Mou et al 2020b ). Haplaxius crudus collected from population surveys in Mexico and Florida tested positive for ‘ Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the vector of LB was identified as the planthopper Haplaxius crudus (Hemiptera: Cixiidae) [3], which is a very widespread and abundant species in Florida and the Caribbean basin (including Mesoamerica and northern South America) [4]. During survey work in Florida in areas with active disease spread, it was demonstrated that populations of H. crudus were higher in areas of LB incidence and appeared to preferentially feed on LB-infected palms over healthy individuals [5]. Furthermore, the difference between LB-infected and healthy trees was demonstrated using a low-cost electronic nose (eNose) [6].…”
Section: Introductionmentioning
confidence: 99%